До питання про курсове проектування під час навчання студентів спеціальності "програмна інженерія" - Васенко, Д. В. (ХНУРЕ, 2022)
We have different students. Most of those admitted to the budget have more than 186 EIT points, which means that they can easily master new material and can complete a course project at the same time as lecturing on that course. At the same time, we have contractors who entered with a much lower score in the external evaluation, and the implementation of the course project at the same time as lecturing on the course is difficult because they can not master the material and do a course project at the same time. It is logical to assume that in this case it makes sense to do a course project not on the subject, but to do in the spring semester a comprehensive course project on the subjects studied during the year